Seguimiento farmacoterapéutico a pacientes con enfermedades crónicas hipertension arterial, diabetes e hipercolesterolemia, en la farmacia escuela maimonides buenos aires, argentina 2007 - Burga Huamán, Jammes Jhonatan (2008)
The Pharmaceutical care is the professional exercise that implies the direct interaction among the pharmacist and the patient in whom both undertake to work together to reach a therapeutic goal. This labor implies detecting, solving and to anticipate the problems related to the medicines (PRM). To lead to end this function it is necessary to establish a plan of attention that implies all those functions directed to help a patient to reach a goal of certain health. This program of Pharmaceutical care led to itself to end in the drugstore school of the Private University Maimónides located in the city of Buenos Aires, Argentina. Besides pharmaceutical advice and sanitary education drank to every patient like diminishing the possible PRMs and complications of the above mentioned diseases. During the year 2007 the follow-up was realized farmacoterapéutico to 34 chronic patients: 21 are only hypertense, 9 are (hypertense and hipercolesterolémicos), 2 are (diabetic and hypertense) and 2 are (hypertense, hipercolesterolémicos and diabetics). Where we observe that 45.8 % of the PRM was problems of need, 29.83 % of efficiency and 25 safeties %. The most frequent PRM was the PRM 1 (Need of a pharmacological additional treatment) and the PRM 4 (Dosage too many fall). By means of a market follow-up of the pharmacological therapy, 24 PRM was detected of which 18 were achieved to resolve. The great importance of our labor as pharmacist and the integration to the equipment of health, allowed to manage to solve 75 % of the PRMs presented in the follow-up.